Proceso de atención de enfermería en paciente hipertenso de 42 años con insuficiencia cardiaca. - Romero Gaibor, Edith Alexandra (2021)
Hypertension with heart failure are diverse clinical syndromes and their physiopathology's are complicated at present they are not fully understood, in most cases they are described to symptomatic patients with hypertensive crisis picture. Taking into account the diversity of clinical manifestations, several different pathological mechanisms are involved, as well as triggers for circulatory decompensation, this clinical case study reviews the pathological evolution of a 42-year-old hypertensive patient with heart failure to describe his symptomatic picture at the time of consultation and boarding taken throughout his hospital stay , for the above-mentioned activities carried out nursing personnel they had an approach based on the model of Marjorie Gordon and its functional patterns which we're of great importance to prioritize discover the needs present in the affected individual, in addition the use of the taxonomic trilogies Diagnosis nurse NANDA, classification and NOC results and nursing interventions NIC , used as basic tools for the realization of the nursing care process that was a tool to provide care in a reasonable, logical way, focused on human responses and I provide the nursing professional with opportunity to identify patterns , it should be noted that the participation of each of the members of the health team contributed a grain of sand to recovery of the patient's health , the achievements of the objectives proposed throughout the process and the integration of the person concerned into society.